The way forward in reforming the legitimate expectations test - Yulia Levashova (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
This Perspective suggests including drafting guidelines for an investor's legitimate expectations under an FET standard into IIAs. The author argues for a more structured methodological approach toward an assessment of legitimate expectations by way of the application of some elements of proportionally. Specific drafting suggestions are proposed.
Keywords: 330